Dependence of efficiency and weights from roller number of rollers. - Бондаренко, Л. Н.; Довбня, Н. П.; Бобырь, Д. В.; Шепотенко, А. П. (Problems of Tribology, 2016)
On the rolling resistance of the wheels and the friction in the bearings has to one of the main components of energy consumption of the rolling stock. For example, overhead cranes installed engine power mechanisms of movement is about 1/3 of the power on the rise.The primary source of reducing energy consumption for traction, as well as to reduce the engine power of the mechanisms of movement, is to improve the bearing in order to increase their efficiency.Analytically receive depending efficiency ball and roller bearings on the number of balls or rollers is hardly possi-ble due to the absence of dependencies to determine the coefficient of rolling friction with the original line and point con-tacts.To determine the rolling resistance of the rollers on the inner and outer races is possible to find the coefficient of rolling friction most downloaded video using the then total load on the bearing.It is shown that the efficiency of ball and roller bearings slightly decrease with increasing number of rollers (balls), roller mass decreases significantly with the increase in the number of rollers, roller bearing and the efficiency is higher than the ball.